Magneto-transport behaviour of Bi2Se3−xTex: role of disorder. (26th January 2016) - Amaladass, E P; Devidas, T R; Sharma, Shilpam; Sundar, C S; Mani, Awadhesh; Bharathi, A
Abstract: Magneto-resistance and Hall resistance measurements have been carried out in fast-cooled single crystals of Bi2 Se3− x Te x ( x   =  0 to 2) in 4–300 K temperature range, under magnetic fields up to 15 T. The variation of resistivity with temperature that points to a metallic behaviour in Bi2 Se3, shows an up-turn at low temperatures in the Te doped samples. Magneto-resistance measurements in Bi2 Se3 show clear signatures of Shubnikov–de Hass (SdH) oscillations that gets suppressed in the Te doped samples. In the Bi2 SeTe2 sample, the magneto-resistance shows a cusp like positive magneto-resistance at low magnetic fields and low temperatures, a feature associated with weak anti-localisation (WAL), that crosses over to negative magneto-resistance at higher fields. The qualitatively different magneto-transport behaviour seen in Bi2 SeTe2 as compared to Bi2 Se3 is rationalised in terms of the disorder, through an estimate of the carrier density, carrier mobility and an analysis in terms of the Ioffe–Regel criterion with support from Hall Effect measurements. We demonstrate that by introducing Te, in the strongly disordered samples a smooth crossover of SdH and WAL can be seen in the Bi2 Se3− x Te x series, both of which provide signatures for the presence of topological surface states.